Urgensi Regulasi Hak Cipta Atas Produk Dari Generative Artificial Intelligence Dalam Menjamin Kepastian Bisnis Industri Kreatif - Nurul Fazri Elfikri; Ramadhan Usman; Akbar Hidayatullah Daud; Nur Insani Aulia (Al-Mizan (e-Journal), 2026)
The rapid development of generative artificial intelligence (AI) is significantly transforming the creative process across creative industries, while also presenting new challenges to copyright law. AI's capacity to produce artwork, music, writing, and designs that mimic human creations raises critical questions regarding authorship, ownership, and the economic rights associated with these outputs. This article examines the need to establish adaptable copyright regulations within the Indonesian legal framework to address the implications of generative AI. Utilizing a normative legal method that incorporates legislative, conceptual, and comparative analyses, the research evaluates national laws, legal doctrines, and international practices. Findings reveal that the existing Indonesian copyright law, which focuses on human creators, inadequately addresses the unique aspects of generative AI, resulting in legal uncertainty. Consequently, there is a pressing need to reformulate copyright laws to ensure legal clarity, protect creators' interests, and foster sustainable technological innovation.